Earth and environmental sciences - Wayne, John (Callisto Reference, 2015)
We have come to face a situation where new environmental troubles arise every day and we need to make some fast and binding decisions. In many cases information regarding geological processes is crucial to find out an appropriate explanation. Earth and environmental sciences is a dynamic field in which new problems arise with time and the old ones often re-emerge. The main aim of this book is to present the readers with a broad overview of Earth and Environmental Sciences by analyzing geology, geochemistry, seismology and hydrology. We are hopeful that this recent research will offer readers with a helpful foundation for discussing and analyzing specific environmental issues and will help in generating new techniques to tackle problems.